2016
DOI: 10.1093/mnras/stw678
|View full text |Cite
|
Sign up to set email alerts
|

Selection bias in dynamically measured supermassive black hole samples: its consequences and the quest for the most fundamental relation

Abstract: We compare the set of local galaxies having dynamically measured black holes with a large, unbiased sample of galaxies extracted from the Sloan Digital Sky Survey. We confirm earlier work showing that the majority of black hole hosts have significantly higher velocity dispersions σ than local galaxies of similar stellar mass. We use Monte-Carlo simulations to illustrate the effect on black hole scaling relations if this bias arises from the requirement that the black hole sphere of influence must be resolved t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
369
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 246 publications
(405 citation statements)
references
References 245 publications
(427 reference statements)
31
369
3
Order By: Relevance
“…However, it has recently been suggested that the black hole sample used to derive scaling relations is likely different from the entire population, leading to a selection bias 25 (Bernardi et al 2007). For instance, using Monte Carlo simulations Shankar et al (2016) recovered the intrinsic scaling relation assuming the selection bias comes from unresolved black holes (e.g. for galaxies with a given velocity dispersion, σ * , it is more difficult to resolve smaller black holes; Batcheldor et al 2010) and showed that such a bias can lead to factors of 3 and ∼50 − 100 higher normalizations of the M bh − σ * and M bh − M * relations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been suggested that the black hole sample used to derive scaling relations is likely different from the entire population, leading to a selection bias 25 (Bernardi et al 2007). For instance, using Monte Carlo simulations Shankar et al (2016) recovered the intrinsic scaling relation assuming the selection bias comes from unresolved black holes (e.g. for galaxies with a given velocity dispersion, σ * , it is more difficult to resolve smaller black holes; Batcheldor et al 2010) and showed that such a bias can lead to factors of 3 and ∼50 − 100 higher normalizations of the M bh − σ * and M bh − M * relations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the observed black-hole scaling relation involving the stellar mass was found to be much more biased than the one involving velocity dispersion (up to an order of magnitude in normalisation), and its apparent tightness could be entirely ascribed to a selection effect. Shankar et al (2016) also suggested that a selection bias more prominent in stellar mass than in velocity dispersion may explain several discrepancies often reported in the literature, i.e. the fact that the observed relation between black-hole and stellar mass predicts a local black-hole mass density two to three times higher than inferred from the relation between black-hole mass and velocity dispersion (e.g., Graham et al 2007;Tundo et al 2007;Shankar et al 2009).…”
Section: Introductionmentioning
confidence: 89%
“…We restrict to this specific SDSS subsample as velocity dispersions in late-type galaxies are not spatially resolved, though the correlation does not depend on the exact cut in p(E+S0). For consistency with the data of Savorgnan et al (2016) to which we will compare, we follow Shankar et al (2016) and correct the velocity dispersions σHL, as in Cappellari et al (2006), to a common aperture of 0.595 kpc (i.e. the one adopted by the Hyperleda data base, Paturel et al 2003).…”
Section: The Normalisation Of the Scaling Relations And The Role Of Smentioning
confidence: 99%
See 2 more Smart Citations